Human Hair Follicular Stem Cell (HHFSC) In Human Hair Follicular Aging - Nadia Permatasari; Adinda Ratulia Suwarno; Adristi Anargya Athallah; Alessandro Isaac Balga; Ammar Soleh Baihaki (Syntax Corporation, 2022)
Aging is considered an inevitable change at different levels of genome, cell, and organism, from the accumulation of DNA damages to imperfect protein homeostasis, altered cellular communication, and exhaustion of stem cells. The decline of regenerative capability caused by the aging process may significantly impact the quality of hair. The aging process affects the hair color, quantity, and quality. Hair becomes thinner and weaker, along with hair graying. These signs of aging may significantly impact some people’s quality of life and lead to depression, anxiety, and other serious mental health problems. In terms of microscopic, the biological problem of aging hair affects biochemical and molecular and changes. Stem cell (SC) exhaustion is one of the hallmarks of aging. This literature review will describe the mechanism of human hair follicular aging and what happens in human hair follicular stem cells.